Combinatorial Processing of Irregular Verbs: Evidence from Aphasia - Stacey Rimikis (Frontiers in Psychology, 2014)
Introduction While semantic and phonological deficits in aphasia are relatively well-studied, less attention has been given to morphological processing. Nevertheless, there are active debates about morphological processing that may be informed by investigating morphological deficits, including the extent to which regular and irregular forms are computed similarly. Theories of processing vary with respect to this point: dual-mechanism accounts propose that regular verbs are computed via rule-based processes combining stems and affixes, while irregular verbs are stored and retrieved separately from their stems. In contrast, full-decomposition accounts posit that both regular and irregular verbs are stored in a decomposed fashion and computed using combinatorial processes. The present study compares the predictions of these two accounts using the single-word reading performance of an aphasic individual with a morphological deficit. We designed two tasks to decouple effects of morphology and phonology and evaluate regular and irregular verb production. In particular, we first compared error patterns of regularly-inflected forms to uninflected homophones (e.g., praise vs. prays) to establish the presence of a morphological deficit. We then compared error rates and types for regularly-inflected (sin-sinned), irregularly-inflected (win-won), and phonologically-matched word pairs (tin-ton). Dual mechanism accounts predict that error rates and types of the irregularly-inflected forms will match the phonological word pairs as all are listed separately in the lexicon. In contrast, full-decomposition accounts predict regular and irregular verbs would demonstrate similar rates and types of morphological errors, distinct from monomorphemic words.